PETA INKLUSI SOSIAL DALAM REGULASI DESA - Dekki Umamur Ra’is (Universitas Tribhuwana Tunggadewi, 2017)
Abstract: Poverty is a typical problem facing rural areas. Problems are increasing with the existence of landlessness, the sharpening of inequality, the weakening of social cohesion, and the escalation of environmental disaster threats. It includes the lack of access to education, health, clean water and environmental sanitation services for marjinalized groups. Poverty is not a major label of the helplessness of a person or a community group. Race, ethnicity, gender, religion, residence (geographical isolation), disabled status, age, HIV/ AIDS status, sexual orientation or other stigma markers may cause a person or a group of societies to be excluded from various processes and opportunities. The exclusion status is inherent as a negative stigma that discriminates people from obtaining basic services and experiences exclusion as being “different”. The Village Law explicitly attempts to transform villages into inclusive villages. The Village Law seeks to end the extreme poverty conditions in villages by applying social inclusive behavior, involving all villagers including marjinalized people. Key Word: Social Inclusion, Regulation, and Participation.